THE IMPACT OF MANAGEMENT COMMUNICATION ON THE DECISIONS TO INCREASE THE PERFORMANCE OF AN ORGANIZATION - TOFAN, Cezarina Adina (Annals of Spiru Haret University. Economic Series, 2016)
: Many Romanian companies going through a difficult period, which makes the care of managers to materialize more on obtaining immediate profit and rarely on some less obvious aspects such as communication influence on labour productivity. Often managers do not consider communication as a factor of real importance that may affect the staff performance. The way we communicate with those around us in the professional activity, but not only, place their mark on the results. Quality of management communication influences the way how the human resource is used and the organizational performance, in particular. Each individual has a certain style of communication formed by education, skills, beliefs and personal goals. It does not always ensure the effective and efficient communication. It can be appreciated the necessity for managers to watch the subordinates, but also to themselves, the change of attitude towards "science communication" by realizing the positive and negative effects of their own style of communication and by raising awareness of the necessity to acquire some communication skills .